2020
DOI: 10.1038/s41598-020-64145-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo efficacy of combinations of colistin and different endolysins against clinical strains of multi-drug resistant pathogens

Abstract: The emergence of multidrug resistant (MDR) pathogenic bacteria is jeopardizing the value of antimicrobials, which had previously changed the course of medical science. In this study, we identified endolysins ElyA1 and ElyA2 (GH108-PG3 family), present in the genome of bacteriophages Ab1051Φ and Ab1052Φ, respectively. The muralytic activity of these endolysins against MDR clinical isolates (Acinetobacter baumannii, Pseudomonas aeruginosa and Klebsiella pneumoniae) was tested using the turbidity reduction assay.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 59 publications
0
53
0
Order By: Relevance
“…Even if no effect of the Rel inhibitor relacin was observed in E. coli, the authors suggested that this could be due to the inability of relacin to penetrate Gram-negative cells and reach its target. However, agents such as polymyxins can destabilize the outer membrane in Gramnegative organisms, facilitating the entrance of therapeutic molecules, e.g., relacin, or endolysins (106). The absence of known (p)ppGpp synthetases in mammalian cells and the specificity of these inhibitors for the Rel protein make this protein a good candidate as an antibacterial agent.…”
Section: Discussionmentioning
confidence: 99%
“…Even if no effect of the Rel inhibitor relacin was observed in E. coli, the authors suggested that this could be due to the inability of relacin to penetrate Gram-negative cells and reach its target. However, agents such as polymyxins can destabilize the outer membrane in Gramnegative organisms, facilitating the entrance of therapeutic molecules, e.g., relacin, or endolysins (106). The absence of known (p)ppGpp synthetases in mammalian cells and the specificity of these inhibitors for the Rel protein make this protein a good candidate as an antibacterial agent.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns in lab animal welfare warrants the possibility of utilizing invertebrate models in expediting the efficacy of antimicrobial agents for preliminary in vivo screening to reduce the candidate molecules for its further evaluation in ethical mammalian models. Having shared the innate immune response to the microbes (Wojda, 2017;Cutuli et al, 2019;Blasco et al, 2020), insects could be selected as suitable alternative models for extrapolating in vitro laboratory findings for probing the potential of Lfcin (17-30) against MDR-EAEC strains. The innate immune system of G. mellonella comprises a progressive cellular as well as humoral response compared to other existing invertebrate models.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathology of the larval model was found closely interrelated with the MDR-EAEC burden, with estimation of various immune markers (melanization, hemocyte density), and with the in vitro time-kill kinetic assays. Additionally, it was concluded that those factors permitting the larval survival could be well pertinent to similar infections in humans ( Sheehan and Kavanagh, 2018 ; Blasco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of bacteriophages in 1915 [ 25 ], they have been used as an alternative treatment for critical bacterial infections, on some occasions even life-threatening [ 26 , 27 ]. In the last decade, i.e., in the post-antibiotic era, the therapy based on lytic phages (phage therapy) or phage derived proteins (enzybiotics) such as, for instance, phage-encoded endolysins [ 28 ], has gained popularity, being one of the few options currently available for infections caused by multi-drug resistant (MDR) bacteria [ 26 , 29 ]. Phages have demonstrated their innocuousness for humans, although some concerns still need to be investigated such as the purity of the preparation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%